Dust modeling over Saudi Arabia using WRF-Chem: March 2009 severe dust case. (October 2015) - Zhang, Yongxin; Liu, Yubao; Kucera, Paul A.; Alharbi, Badr H.; Pan, Linlin; Ghulam, Ayman
Abstract: This paper documents the performance of the fully coupled WRF-Chem model at 21.6 km and 7.2 km resolution over Saudi Arabia in simulating a severe dust storm event that occurred in March 2009. The comparisons between the model simulations and the observed AOD at the Solar Village AERONET site and the MODIS measurements show that WRF-Chem satisfactorily resolves the arrival, evolution and spatial distributions of the dust storm over Saudi Arabia especially for the fine domain at 7.2 km resolution. The model simulated surface meteorological variables at Riyadh Airport, Hafr Al-Batin Airport, Dammam Airport and Gassim Airport follow the observations in terms of magnitude and temporal evolution although model biases such as deficiencies in simulating the amplitude of diurnal cycles are noted. Higher resolution and shorter initialization time improve the model performance in aerosol optical depth but for surface variables shorter initialization time improves correlation while higher horizontal resolution improves mean biases to some extent. The simulated dust plume is mainly confined between the surface and the 5-km height, with the peak concentrations located in the lowest 500 m. The vertical extent of the dust plume shows gradual decreases during the simulation period when averaged over the entire fine domain and an area centered around Solar Village, and also varies in accordance with the development and decay of the boundary layer. Highlights: WRF-Chem simulates temporospatial distributions of observed dust reasonably well. Finer resolution performs better for AOD but with mixed results for meteorology. Dust plume is confined between the surface and the 5-km height. Vertical extent of dust plume varies in accordance with the boundary layer.